Practical learning styles approach on Personalised Learning Environment (PLE) - Che Ku Mohd, Che Ku Nuraini (UTeM, 2016)
Personalised Learning Environment (PLE) is one of the learning approaches that help learners take control of and manage their own learning towards flexible and adaptive in responding to the diverse needs and interests of students. However, there are limited research conducted that integrates learning styles with PLE approach using prototype to increase student performance. Learning styles are important components in a learning environment. Learning styles are among the concepts that are postulated by to show learners’ differences and varied needs. The issues in this study highlight students’ lack of interest in learning Science and also fail to classify, synthesise and evaluate information. There are three objectives which are (i) To propose a learning model that integrate dominant learning styles and PLE elements; (ii) To design a learning prototype based on the proposed model that integrates dominant learning styles in Personalised Learning Environment (PLE) and (iii) To evaluate the effectiveness of the prototype towards student performance and student perception. Science is a compulsory subject for Form 2 students from Ministry of Education Malaysia. A prototype called PLENut was developed. The research framework consist of three phases which are (i) Phase 1 PLENut Analysis, (ii) Phase 2: PLENut Design, Development & Implementation and (iii) Phase 3: PLENut Evaluation. Testing was conducted to analyze independent variables by Visual, Auditory and Kinesthetic types of learning styles while student’s performances and student perception are dependent variable. The data was populated from 132 Form Two students of Sekolah Menengah Kebangsaan Dato' Dol Said, Alor Gajah, Melaka, Malaysia. The population was divided into 3 groups which is (i) Visual (n=76); (ii) Auditory (n=35) and (iii) Kinesthetic (n=21). The separate sample pretest and posttest design was implemented to assess the effectiveness of the PLENut in increasing students’ performance. Non parametric tests which are Wilcoxon Signed Ranked Test and Kruskal Wallis Test were used to analyze the data. The result revealed that: (i) there were no statistically significant differences in mean ranks between group 1, group 2 and group 3 for Visual, Auditory and Kinaesthetic learning styles in terms of student performance and (ii) there were two specific learning styles that were statistically different from each other, which is between Kinesthetic-Visual (test statistic=60.650, p-value=0.000) and Auditory-Visual (test statistic=45.440, p-value=0.000). Therefore, the study found that there is a significant relationship between student performance and learning styles. Results of student performances showed that Science subject is significant with Visual, Auditory and Kinaesthetic learning styles. As a conclusion, PLENut has demonstrated a practical learning styles approach on Personalised Learning Environment (PLE) in teaching and learning of Science subject.